Are article 9 funds superior? A comprehensive empirical analysis of the SFDR regulation on its efficacy, flows and performance - Lindemann, Jost Christoph (2023)
This master's dissertation examines the impact of the Sustainable Finance Disclosure Regulation (SFDR) on mutual equity funds domiciled in the Eurozone, specifically those governed by Article 9, and the ensuing behavioural repercussions on investors. This academic endeavour contributes to the growing empirical evidence positing the SFDR regulation as an effective bulwark against greenwashing. This is substantiated through the analysis of cross-sectional data procured from two independent ESG data providers, Refinitiv and MSCI, demonstrating that funds governed by Article 9 consistently deliver superior ESG metrics. Further, this dissertation probes the propensity of investors to allocate a greater quantum of capital towards Article 9 funds and ventures into a detailed analysis of the inherent characteristics of these investors. Utilising a panel data dataset and deploying a difference-in-differences model revealed that investors demonstrate a preference for Article 9 funds preceding the final implementation date of 10th March 2021. Additionally, these investors exhibit signs of higher resilience. Lastly, this research assesses performance disparities by deploying the Fama and French 3-Factor Model. The analysis suggests that Article 9 funds are characterised by heightened factor exposure to growth investments. Nevertheless, during the observation period spanning 2018 to 2022, SFDR 9 funds do not exhibit a positive alpha. However, when assessed through a difference-in-differences lens, these funds demonstrate a significantly higher alpha than their counterparts.